Principios y reglas de solución aplicables a las controversias territoriales a la luz de la jurisprudencia de la Corte Internacional de Justicia (2014)
Unfortunately territorial conflicts are a constant in international relations, being of great importance that they are settled in a peaceful way. The work of the International Court of Justice in this regard has been fundamental. Its extensive jurisprudence in this area has generated a number of principles and rules on which this arrangement is based, such as the principle of continuity of territorial treaties, the principle of uti possidetis iuris, the primacy of legal title, the relativity of the effectiveness, or the critical date. The knowledge of these principles and rules is essential for future arrangements.